Pembelajaran Pendidikan Agama Islam Kontekstual di Sekolah Dasar Alam - Tri Era Khoiriyah; Hakiman Hakiman; Aminudin Aminudin (Program Studi PGMI STAI Daruttaqwa Gresik, 2021)
This article attempts to examine the implementation of Islamic Education Through Contextual Learning on Bengawan Solo Alam Elementary School, Klaten. Teachers as educators should present am Islamic Education learning which is packaged attractively so that students not only understand the learning cognitively but also have behavioral enlightenment and apply it in daily life. The research is field research, that is research field where researchers present directly in the research. Data collection techniques used are observation, interview, documentation, and Group Discussion. Data validation techniques used are triangulation technique, sources, and methods. Data analysis techniques start on the reduction of the data, presentation of data, and then drawing conclusions. The result of this article showed that the implementation of Islamic Education contextual learning in Bengawan Solo Alam Elementary School through: 1) integration to all subjects, 2) take advantage of nature 3 ) prioritizing practice and experience, 4) exemplary and habituation, 5) associate with local culture. Learning activities supported by: gardening, outing class, dhuha prayer before learning, congregational prayer at the village mosque, and social activities.